Business Development Through Socialization and Assistance Related to Licensing (Legality) of MSMEs in Sugihwaras Village Area, Candi District, Sidoarjo Regency - Devinta Nur Arumsari; Fani Khoirotunnisa; Virginia Mandasari (Future Science, 2022)
Sugihwaras is a settlement in East Java, Indonesia's Sidoarjo Regency, Candi Subdistrict. The majority of residents of the community of Sugihwaras make their living through their businesses. Temporary observations in Sugihwaras Village, Candi District, indicate that the local community's companies 1) lack trademarks, 2) lack NIBs (Business Registration Numbers), and 3) improperly apply marketing concepts. To help the public understand how people may become entrepreneurs by optimizing the items they sell utilizing various marketing efforts, such as through social media. The transfer of information using focus groups, presentations, and exercises or practices as part of the implementation process A legal document is the by-product of this mentoring activity for each MSMEs member in the Sugihwaras village region, Candi sub-district, and Sidoarjo Regency. Additionally, a module is created as part of the development of the micro-enterprise home industry on how to create a business legality document. The service's outcomes will be documented in a monograph and registered as intellectual property rights after that (IPR).